Turkish Hazelnut Extracts Exert Anti-Proliferative and Anti-Cancer Effects on Colorectal Cancer HCT-116 Cells - Bayram, Banu; Demircan, Evren; Karimidastjerd, Atefeh; Akyuz, Elvan Yilmaz; Tutar, Yusuf (MDPI, 2025)
The rising incidence of cancer has demanded the development of new anti-cancer chemical sources. The presence of phenolics in hazelnut cell cultures has led to the development of new and potential pharmacotherapeutic uses. Hazelnut extract has emerged as a promising candidate due to its high phytochemical content. HCT-116 colorectal cancer IC50 cell viability of Palaz and Tombul hazelnut extracts was determined as 400 mu g/mL and 200 mu g/mL, respectively. Flow cytometry annexin V-fluorescein isothiocyante (FITC) apoptosis detection indicated apoptosis of Tombul hazelnut extract and Palaz hazelnut extract as 23.53% and 17.47%, respectively. The apoptosis result of flow cytometry was also supported at the protein level. Hazelnut extracts resulted in an increased loss of MMP as well. The loss of MMP has significantly increased from an average of 0.61% to 16.17% in Tombul hazelnut extract and to 20.38% in Palaz hazelnut extract. This is further supported by screening MICU1, MICU2, PPAR-gamma, PPARGC1A, UCP1, UCP2, and UCP3 gene expressions. Targeting apoptosis pathways, particularly MMP, is an effective strategy for cancer prevention and treatment. Hazelnut extract contains phenolic compounds, which activate these pathways, resulting in enhanced apoptosis in colorectal cancer cells. The phenolic contents of Palaz and Tombul hazelnut extracts were determined as 271.72 +/- 5.3 mg gallic acid equivalent (GAE)/100 g sample dry weight (DW) and 85.23 +/- 2.2 mg GAE/100 g sample DW, respectively. Further, hazelnut extract may reduce oxidative stress, contributing to its anti-cancer properties. The extracts could be utilized as functional ingredients in foods and nutraceuticals to assist with cancer prevention and treatment.
Keywords: anticancer; apoptosis; colorectal cancer; hazelnut extract; mitochondrial membrane potential; PHENOLIC-COMPOUNDS; MITOCHONDRIAL DYSFUNCTION; OXIDATIVE STRESS; PROLIFERATION; VARIETIES; GROWTH; SHELL; Biochemistry & Molecular Biology